1910
DOI: 10.5962/bhl.title.110688
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance of the geology and mineral resources of Prince William Sound, Alaska,

Abstract: Duchess tunnel, Latouche Island 8. Bald Eagle tunnel, Knight Island 9. Tunnel cutting five schistose ore-bearing zones, Knight Island 6 The important fact bearing on the distribution of the ore bodies is that they appear to be found only in the rocks of the Orca group and, indeed, for the most part in close association with the greenstone member. Mr. Grant and Mr. Higgins indicate that the copper was derived from the greenstones, a genesis which is entirely similar to that of most of the copper ores of the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1954
1954
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Seven copper prospects also reported by them to be active on Glacier Island and on the mainland to the north. In 1913 Johnson (1916) reported that only six properties were active--only two Were previously discussed by Grant and Higgins (1910). By 1917 there was little if any work being done on the prospects.…”
Section: History Of Mineral Activitymentioning
confidence: 99%
“…Seven copper prospects also reported by them to be active on Glacier Island and on the mainland to the north. In 1913 Johnson (1916) reported that only six properties were active--only two Were previously discussed by Grant and Higgins (1910). By 1917 there was little if any work being done on the prospects.…”
Section: History Of Mineral Activitymentioning
confidence: 99%
“…(2) There is a major terrane boundary, but, at least in the western part of Prince William Sound, it is not located along the Contact fault. If this terrane boundary is to separate Cretaceous from Paleogene rocks, it would have to fall somewhere between the Contact fault and the Orca-Valdez contact as mapped by Grant and Higgins (1910) and Moffit (1954) (fig. 4).…”
Section: Petrographic Constraints On the Significance And Location Ofmentioning
confidence: 99%
“…Early workers originally assigned to the Orca Group rocks of the islands east of Bainbridge and Knight Island Passages, the rocks of Naked and Glacier Islands, and rocks of the mainland adjacent to Orca Bay, Port Gravina, and Port Fidalgo (Grant and Higgins, 1910) (fig. 4).…”
Section: The Contact Fault Systemmentioning
confidence: 99%
“…I n c l u d e s r e f e r e n c e s t o E l l i s I m p e r i a l . Grant and Higgins, 1910 (B 4 4 3 ) , p . 74-75 --Adit d r i v e n from a p o i n t n e a r sea l e v e l along v e i n f o r more than 100 ft.…”
Section: Prince W I L L I a M Sound D I S T R I C Tmentioning
confidence: 99%